Fundamentals of soil ecology - Coleman, David C. (Academic Press, 1996)
This graduate level text reference is designed to be a bridge between ecologists and soil scientists. There is increasing awareness that soil is the organizing center for all terrestrial ecosystems. This text examines why this is so, in terms of the physics, chemistry, and biology of soil ecosystems. Biodiversity and global change and the important role soils play in global carbon balance are also discussed.